Hyrax versus transverse sagittal maxillary expander: An assessment of arch changes on dental casts. A retrospective study - C. Maspero; D. Cavagnetto; A. Fama; L. Giannini; G. Galbiati; M. Farronato (Saudi Dental Journal)
Objective: The aim of this study was to compare arch changes before and after maxillary expansion with Transverse Maxillary Sagittal Expander (TSME) and Hyrax Palatal Expander (HPE), in growing patients with diagnosis of maxillary hypoplasia. Materials and methods: The sample consisted of 40 patients’ records (20 males 20 females mean age 9.2 ± 2.6 years) were selected from the archive of the Orthodontic Department of the University of Milan, Italy. Patients were randomly divided in two groups: patients in group 1 were treated with HPE as they presented only transverse deficiency of the maxilla and in group 2 were treated with TSME. Plaster models have been measured with a Verniere caliper to evaluate the differences in maxillary expansion of the two devices. Measurements were performed on casts poured from impressions taken before appliance bonding (T0), immediately after appliance debonding (T1) and at 6 months follow-up (T2). The variations in the following distances have been considered: inter-molar distance, inter-canine distance, palatal depth, palatal length and arch circumference. Shapiro-Wilk test was performed to assess normality distribution. ANOVA for repeated measures with multiple paired t-test for pairwise comparisons and its non-parametric equivalent Friedman’s test with multiple Wilcoxon tests for pairwise comparisons were performed to evaluate changes in time of each variable in each group. Between groups comparisons were performed for each variable at each observing time using independent t-test or Mann-Whitney test. Significance level was set at p < 0,05. Results: Both the Friedman test and the rm-ANOVA test and their respective post-hoc show that within both groups the respective variables have a statistically significant increase between T0 and T1 (p < 0,05) and a slight decrease between T1 and T2 (p < 0,05) that is not clinically relevant remaining always T2 greater than T0 in a statistically and clinically relevant way (p < 0,05). The analysis between the differences of the measurements at different timing measured by the Mann-Whitney test shows that for all the variables there is no statistically significant difference between the 2 devices (p < 0,05), except for the perimeter of the arch and the length of the palate; in this case it appeared that the TSME is better statistically (p < 0,05). Conclusions: The study has shown that RPE and TSME can achieve similar results in transversal palatal expansion. Differences have been found in the palatal length and in the arch perimeter where TSME seems to be more efficient. Keywords: Rapid maxillary expansion, Transverse sagittal maxillary expander (TSME), Maxillary hypoplasia, Cross bite